2000
DOI: 10.1046/j.1365-2168.2000.01535.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of preoperative portal vein ligation on endotoxin-induced hepatic failure in hepatectomized rats is associated with reduced tumour necrosis factor α production

Abstract: Prevention of endotoxin-induced liver failure by preoperative PVL is associated with reduced production of TNF-alpha in the later phase of liver regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…14 However, in an experimental model, Krupski et al 24 showed that the increase of liver volume after PVL was not restrained by the formation of porto-portal collaterals. The fortnight normalization of increased portal blood flow induced by portal vein occlusion in humans 25 and the early peak of hepatocyte proliferation after portal occlusion in rodents 26,27 suggest that liver hypertrophy is early induced after portal occlusion. Then, later formation of porto-portal collaterals would not impact on the induced liver hypertrophy.…”
Section: Discussionmentioning
confidence: 97%
“…14 However, in an experimental model, Krupski et al 24 showed that the increase of liver volume after PVL was not restrained by the formation of porto-portal collaterals. The fortnight normalization of increased portal blood flow induced by portal vein occlusion in humans 25 and the early peak of hepatocyte proliferation after portal occlusion in rodents 26,27 suggest that liver hypertrophy is early induced after portal occlusion. Then, later formation of porto-portal collaterals would not impact on the induced liver hypertrophy.…”
Section: Discussionmentioning
confidence: 97%
“…The increased portal blood flow induced by portal vein occlusion seems to normalize in 2 weeks, with early peak of hepatocyte proliferation after portal occlusion, suggesting that liver hypertrophy is induced early after portal occlusion. [37][38][39] Then, later formation of portoportal collaterals would not impact on the induced liver hypertrophy. This process may explain the comparable increase in FLR with both techniques in the majority studies.…”
Section: Discussionmentioning
confidence: 98%
“…They explained that one of the reasons for the larger liver volumes is the portoportal collateral vessels. However, as in other several studies, fortnight normalization of increased portal blood flow induced by portal vein occlusion in humans and the early peak of hepatocytes proliferation after portal occlusion in rodents suggests that liver hypertrophy after portal occlusion is induced earlier than the formation of portoportal collateral formation (19)(20)(21). Hence, this may have little impact on liver hypertrophy.…”
Section: Discussionmentioning
confidence: 84%